The role of entrepreneurial passion in strengthening entrepreneurial intention through self-efficacy and leadership in Batam City - Shinta Wahyu Hati; Erika Priyanti Nainggolan (Pusat P2M Politeknik Negeri Batam, 2026)
This research examines the role of entrepreneurial passion in shaping entrepreneurial intention, with self-efficacy and leadership considered as mediating factors among micro, small, and medium enterprise (MSME) owners in Batam City. Using a quantitative survey approach, data were collected from 306 respondents and analyzed with Partial Least Squares–Structural Equation Modeling (PLS-SEM) through SmartPLS 4. The results demonstrate that entrepreneurial passion exerts a significant positive influence on self-efficacy, leadership, and entrepreneurial intention. In addition, both self-efficacy and leadership contribute meaningfully to strengthening entrepreneurial intention. These findings underline the importance of psychological aspects in stimulating entrepreneurial behavior and supporting business growth. The study enriches the entrepreneurship literature by presenting an integrated model of entrepreneurial passion, self-efficacy, leadership, and entrepreneurial intention, while also offering practical insights for policymakers to inform MSME development strategies that enhance entrepreneurial capacity and ensure long-term sustainability.